Keanekaragaman Genetik Rayap Tanah Genus Coptotermes (Isoptera: Rhinotermitidae) di Pulau Jawa - Niken Subekti; Dodi Nandika; Dedy Duryadi Solihin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2006)
Subterranean termite Coptotermes spp. has been known as the most economically important structural pest in Indonesia. Due to morphological ambiguity, traditional identification of Coptotermes spp. has always been difficult and unreliable.  Through molecular diagnostic method, a study was conducted to determine genetic variation of Coptotermes spp. occurring in Java Island.  Termite specimens were collected from Banten 1, Banten 2, DKI 1, DKI 2, Jabar 1, Jabar 2, Jateng 1, Jateng 2, Yogya 1, Yogya 2, Jatim 1, and Jatim 2.  The method for identification was PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) analysis using four restriction enzymes each of which was applied to CO II amplicon for all the Coptotermes spp. being analyzed.  The results showed the existence of two species of Coptotermes in Java which are different from both Coptotermes gestroi and Coptotermes formosanus.